Modified ammonium polyphosphate flame retardant as well as preparation method and application thereof

By using metal organic frame material and sodium lignin sulfonate to modify ammonium polyphosphate, an organic and inorganic hybrid core-shell structure is formed, which solves the problem of degradation in high humidity environments and significantly improves the rigid polyurethane The mechanical and flame retardant properties of the foam and reduce the amount of smoke released, achieving higher environmental friendliness.

CN119241914APending Publication Date: 2025-01-03ZHANGJIAGANG CHANGTAI AUTO TRIM MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411254240.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing ammonium polyphosphate flame retardants have poor moisture resistance and poor compatibility with the polyurethane material matrix in high humidity environments, resulting in a decrease in mechanical, thermal insulation, flame retardant and smoke suppression properties.

Method used

By using the metal organic frame material ZIF-67 and sodium lignin sulfonate to chemically modify ammonium polyphosphate, an organic inorganic hybrid core-shell structure is formed, which improves its moisture resistance and compatibility with polyurethane materials, and is also used to MDI and The crosslinking agent forms a mesh polyurethane structure, enhancing its flame retardant properties.

Benefits of technology

It significantly improves the mechanical strength of rigid polyurethane foam materials, reduces thermal conductivity, improves the limit oxygen index and reduces the total smoke output, and the flame retardant is halogen-free and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241914A_ABST
    Figure CN119241914A_ABST
Patent Text Reader

Abstract

The invention relates to a modified ammonium polyphosphate flame retardant as well as a preparation method and application thereof. The problems that ammonium polyphosphate is poor in moisture resistance and poor in compatibility with a polyurethane material matrix, so that the mechanical performance, the heat preservation performance, the flame retardance and the smoke suppression performance are reduced are mainly solved. By adopting the technical scheme of a novel modified ammonium polyphosphate flame retardant, the technical problem is well solved, and the modified ammonium polyphosphate flame retardant can be used in a rigid polyurethane foam material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified ammonium polyphosphate flame retardant and a preparation method and application thereof. Background Art

[0002] As a thermal insulation material, rigid polyurethane (RPU) foam is widely used in houses, refrigerators and transportation industries. However, RPU foam without flame retardant treatment is flammable and can release a large amount of toxic smoke, causing casualties. Although traditional halogen flame retardants can effectively improve the flame retardant properties of RPU foam, halogen-containing compounds will release toxic acidic smoke and accumulate biological hazards when they play a flame retardant role. Some halogen flame retardants have been banned or gradually replaced. Ammonium polyphosphate (APP) is a common nitrogen-phosphorus-based intumescent flame retardant. Due to its low price, low toxicity and high efficiency, it has become the focus of flame retardant research in recent decades. APP is rich in nitrogen and phosphorus elements, which can provide gas source and acid source for the expansion system respectively. It is often used in combination with carbon source substances to enhance its carbonization ability. The flame retardant mechanism of APP is: ammonium polyphosphate decomposes into phosphate substances when heated, among which the strongly acidic phosphate catalyzes the matrix to produce a dehydration reaction to produce carbonized products, and decomposes to produce non-flammable gases such as NH3 to dilute oxygen, and expands the residual carbon to form a carbon layer barrier. It can form an expanded carbon layer together with some carbon-forming agents or carbon-forming groups, which can block the transfer of heat and oxygen and protect the inner layer of the polymer material when the polymer material is exposed to fire.

[0003] Although APP has the above advantages, it is moisture-sensitive and easily seeps out of the matrix in a high humidity environment, resulting in a decrease in flame retardant efficiency. At the same time, as an inorganic additive flame retardant, it has poor compatibility with the polyurethane matrix. As the amount added increases, it is often easy to cause the mechanical and thermal insulation properties of the polyurethane material to decrease. These shortcomings limit the application of APP. Therefore, it is necessary to modify APP to improve its performance.

[0004] The zeolitic imidazole ester framework compound formed by the self-assembly of the transition metal element Co and the organic ligand containing the imidazole ring is not only easy to synthesize, but also has a multifunctional network structure, a large specific surface area and high surface activity, which gives it high catalytic activity and good chemical stability. The molecular structure of lignin contains rich aromatic rings and aliphatic groups, with a carbon content of more than 60%, which can make up for the lack of carbon source in APP and enhance the carbonization of APP. As a by-product of the papermaking industry, lignin is easy to obtain as a raw material and is green, environmentally friendly and sustainable. In addition, the lignin structure contains a variety of active groups, such as alcoholic hydroxyl groups and phenolic hydroxyl groups, which are the key reaction sites for chemical modifications such as amination and graft copolymerization, thus providing the possibility for further chemical modification. The development and application of lignin-based flame retardants are conducive to protecting human health and the green and sustainable development of the flame retardant field.

[0005] Chinese patent CN 117603501A discloses a melamine ammonium polyphosphate flame retardant containing metal catalytic function and its preparation method, wherein ammonium polyphosphate and cobalt nitrate hexahydrate are mixed and added to an organic solvent, and 2-methylimidazole organic solution is added after stirring and the reaction is continued; after the reaction is completed, the reaction solution is vacuum filtered, washed, and dried in sequence to obtain a powdered precursor; melamine, bisphenol A, and polyformaldehyde are mixed and added to an organic solvent, and refluxed and stirred under heating conditions to generate a coating body; after a period of reaction, the above precursor is added and the reaction is continued; the temperature is then raised for reflux reaction; after the reaction is completed, the reaction product is poured out, dried, and crushed to obtain a melamine / ammonium polyphosphate flame retardant containing metal catalytic function. The flame retardant prepared by this method has a good flame retardant effect, but its preparation process is complicated and formaldehyde is used in the reaction raw materials, which is not healthy and environmentally friendly and is harmful to humans. Summary of the invention

[0006] One of the technical problems to be solved by the present invention is the problem of poor moisture resistance of ammonium polyphosphate in the prior art and its poor compatibility with a polyurethane material matrix, which causes decreased mechanical, thermal insulation, flame retardant and smoke suppression properties. A new modified ammonium polyphosphate flame retardant is provided, which can prepare a rigid polyurethane foam material with higher mechanical, thermal insulation, flame retardant and smoke suppression properties.

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing a modified ammonium polyphosphate flame retardant corresponding to the first technical problem to be solved.

[0008] The third technical problem to be solved by the present invention is to provide a use of a modified ammonium polyphosphate flame retardant corresponding to the first technical problem to be solved.

[0009] In order to solve one of the above technical problems, the technical solution adopted by the present invention is as follows: a modified ammonium polyphosphate flame retardant, whose structural formula is as follows:

[0010]

[0011] Wherein, R1 is sodium lignin sulfonate, and R2 is selected from One of the following, R3 is

[0012] In order to solve one of the above technical problems, the technical solution adopted by the present invention is as follows: a method for preparing a modified ammonium polyphosphate flame retardant, comprising the following steps:

[0013] (1) Add 44.7-74.5 parts by mass of ammonium polyphosphate, 14.6-29.1 parts by mass of cobalt nitrate hexahydrate and 300-500 parts by mass of reaction solvent I into a reaction vessel, and stir for 1-3 hours at room temperature to obtain material I;

[0014] (2) Add 20.5 to 82.1 parts by mass of 2-methylimidazole to material I, stir for 8 to 12 hours at room temperature, filter, dry, and sieve to obtain material II;

[0015] (3) Add 48.7-72.4 parts of material II, 8-20 parts of MDI and 300-500 parts of reaction solvent II into a reaction vessel by mass, evacuate the vessel, introduce inert gas, and stir under heating conditions for 1-3 hours to obtain material III;

[0016] (4) Add 1 to 5 parts of a cross-linking agent and 8 to 30 parts of sodium lignin sulfonate to material III by weight, evacuate the mixture, introduce an inert gas, and stir under heating conditions for 6 to 8 hours to obtain material IV.

[0017] (5) After the reaction is completed, the product is filtered, dried, and sieved to obtain a modified ammonium polyphosphate flame retardant product.

[0018] In the above technical solution, preferably, the reaction solvent I in step (1) is selected from one of methanol and ethanol.

[0019] In the above technical solution, preferably, the drying temperature in step (2) is 60-80° C., the filtration needs to be performed three times with solvent I, and the mesh size of the sieve used during sieving is 80-100 meshes.

[0020] In the above technical solution, preferably, the reaction solvent II in step (3) is selected from one of ethyl acetate and dichloromethane, and the reaction is carried out under the protection of an inert gas, and the reaction temperature is controlled at 50-70°C.

[0021] In the above technical solution, preferably, the cross-linking agent in step (4) is selected from one of propylene glycol and pentaerythritol, and the reaction is carried out under the protection of an inert gas, and the reaction temperature is controlled at 60-80°C.

[0022] In the above technical solution, preferably, the filtering in step (5) needs to be performed three times with reaction solvent II, the drying temperature is 50-70° C., and the mesh size of the sieve used during sieving is 80-100 meshes.

[0023] To solve the third of the above technical problems, the technical solution adopted by the present invention is as follows: application of a modified ammonium polyphosphate flame retardant in a rigid polyurethane foam material.

[0024] The present invention provides a modified ammonium polyphosphate flame retardant, which uses a metal organic framework material (ZIF-67) and sodium lignin sulfonate to modify the surface of ammonium polyphosphate through a chemical reaction to obtain a modified ammonium polyphosphate flame retardant with an organic-inorganic hybrid core-shell structure. The compound simultaneously has three flame retardant elements of carbon, nitrogen and phosphorus, wherein the metal organic framework material (ZIF-67) not only has a catalytic function, but also has a good smoke absorption effect due to its large specific surface area; the mesh polyurethane structure formed by lignin and MDI can improve the moisture resistance of ammonium polyphosphate and provide sufficient carbon source for the expansion flame retardant system. Compared with unmodified ammonium polyphosphate, the flame retardant has excellent moisture resistance, compatibility with the substrate and smoke suppression performance. The flame retardant is halogen-free and also has biomass material lignin, which improves the environmental friendliness of ammonium polyphosphate. When the flame retardant is applied to rigid polyurethane (RPU) foam, compared with ammonium polyphosphate, the mechanical strength of the rigid polyurethane foam is increased by 27.0%, the thermal conductivity is reduced by 9.8%, the limiting oxygen index is increased by 16.3%, and the total smoke production is reduced by 58.9%, achieving good technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM images of ammonium polyphosphate (APP) and modified ammonium polyphosphate (APP@ZL) proposed in the present invention;

[0026] Figure 2 The particle size distribution diagram and FT-IR spectrum diagram of APP and APP@ZL proposed in the present invention;

[0027] Figure 3 XPS spectra of APP and APP@ZL proposed in the present invention;

[0028] Figure 4 TG curves of APP and APP@ZL proposed in the present invention under N2 atmosphere;

[0029] Figure 5 TG curves of the pure rigid polyurethane foam material (RPU) proposed in the present invention, the rigid polyurethane foam material of Comparative Example 1 (B1) and Example 9 under N2 atmosphere

[0030] Figure 6 It is a graph of the total amount of smoke released by the rigid polyurethane foam materials of Examples 7 to 12 and Comparative Example 1 proposed by the present invention;

[0031] Figure 7 The total heat release diagram of the rigid polyurethane foam materials of Examples 7 to 12 and Comparative Example 1 proposed by the present invention

[0032] Figure 8 The invention discloses a preparation process of the modified ammonium polyphosphate (APP@ZL). DETAILED DESCRIPTION

[0033] The following are only preferred implementations of the present invention, and are not intended to limit the scope of protection of the present invention. All technical solutions within the scope of the present invention should fall within the scope of protection of the present invention. For professional and technical personnel in this technical field, minor improvements and modifications to the present invention without departing from the principles of the present invention should also fall within the scope of protection of the present invention.

[0034] Table 1 List of raw materials

[0035] Raw material types Disk number factory Ammonium Polyphosphate A823395 Shanghai MacLean Biochemical Technology Co., Ltd. Polyether polyols LY-4110 Wanhua Chemical Group Co., Ltd. Silicone oil AK-8809 Demei Chemical Co., Ltd. Dibutyltin dilaurate T-12 Jiangsu Yixing Yake Chemical Co., Ltd. Hydrofluorocarbons HFC-365mfc Shanghai Ruiyi Environmental Protection Technology Co., Ltd. MDI PM200 Wanhua Chemical Group Co., Ltd.

[0036] [Example 1]

[0037] A modified ammonium polyphosphate flame retardant, the preparation method of which comprises the following steps:

[0038] (1) 60 parts of ammonium polyphosphate, 14.6 parts of cobalt nitrate hexahydrate and 300 parts of methanol were added into a reaction vessel and stirred for 2 hours at room temperature to obtain material I;

[0039] (2) Add 20.5 parts of 2-methylimidazole to material I, stir at room temperature for 12 hours, filter, dry, and sieve to obtain material II;

[0040] (3) Add 50 parts of material II, 10 parts of MDI and 300 parts of dichloromethane into a reaction vessel, evacuate the vessel and introduce inert gas protection, and stir for 2 hours under heating conditions to obtain material III;

[0041] (4) Add 1 part of propylene glycol and 10 parts of sodium lignin sulfonate to material III, evacuate the mixture, introduce inert gas protection, and stir for 6 hours under heating conditions to obtain material IV.

[0042] (5) After the reaction is completed, the mixture is filtered, dried, and sieved to obtain modified ammonium polyphosphate flame retardant S1.

[0043] [Examples 2 to 6]

[0044] Examples 2 to 6 are carried out according to the steps in Example 1, except for the differences in reaction raw materials, raw material ratios, reaction time, and reaction temperature, as shown in Table 2; the performance data of the obtained modified ammonium polyphosphate flame retardant product and unmodified APP are shown in Table 4.

[0045] Table 2 Raw material mass fractions and reaction conditions in the preparation of modified ammonium polyphosphate flame retardants in Examples 1 to 6

[0046]

[0047] [Example 7]

[0048] Preparation of component A: 100 parts of LY-4110, 1.2 parts of T-12, 45 parts of flame retardant S1, 25 parts of HFC-365mfc and 2 parts of AK-8809 were stirred at a speed of about 1300 rpm for 3 minutes to prepare a uniform component A.

[0049] Subsequently, 120 parts of PM200 were added to component A and stirred at a speed of about 2500 rpm for 10 seconds. The stirred mixed solution was quickly poured into an open mold. After the foaming was completed, the foam was placed in an oven at 75°C for aging for 5 hours to obtain a rigid polyurethane foam material. The index data of the obtained rigid polyurethane foam material are shown in Table 5.

[0050] [Examples 8 to 12]

[0051] Examples 8 to 12 are carried out according to the steps in Example 7, except that different modified ammonium polyphosphate flame retardants are used. The flame retardants used in Examples 8 to 12 are modified ammonium polyphosphate flame retardants S2 to S6, and the specific components are shown in Table 3; the index data of the obtained rigid polyurethane foam material are shown in Table 5.

[0052] [Comparative Example 1]

[0053] Comparative Example 1 was carried out according to the steps of Example 7, except that the flame retardant used was unmodified APP. The specific composition is shown in Table 3; the index data of the prepared rigid polyurethane foam material are shown in Table 5.

[0054] Table 3 Weight percentage of each component added to the polyurethane foaming formula by flame retardant in Examples 7 to 12 and Comparative Example 1

[0055] serial number Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Comparative Example 1 Flame retardants 45 45 45 45 45 45 45 LY-4110 100 100 100 100 100 100 100 AK-8809 2 2 2 2 2 2 2 T-12 1.2 1.2 1.2 1.2 1.2 1.2 1.2 HFC-365mfc 25 25 25 25 25 25 25 PM200 120 120 120 120 120 120 120

[0056] Table 4 Water leaching rate of Examples 1 to 6 and APP flame retardant

[0057]

[0058] Note: Test method for water leaching rate of flame retardants: Since the soluble particles of flame retardants can be dissolved in water and leached through filter paper, the specified water leaching rate is used to characterize its water solubility. About 10g of flame retardant is marked as W1 and packaged together with the same filter paper marked as W2. The sample is placed in about 1L of distilled water and kept at different temperatures for 48h, then taken out and dried at 80℃ to constant weight and marked as W3; the water leaching rate of the sample can be expressed as: Water leaching rate = (W3-W2) / (W1-W2)×100%

[0059] Table 5 Index data of rigid polyurethane foam materials of Examples 7 to 12 and Comparative Example 1

[0060]

[0061] From the water leaching rate data in Table 4, it can be seen that at 25°C, the water leaching rate of APP is 97%, and at higher temperatures, the water leaching rate of APP can reach 100.0%, which shows that APP is easily affected by moisture when in use. The water leaching rates of S1 to S6 are much less than that of APP. This shows that the water resistance of S1 to S6 is far superior to that of APP, which is attributed to the esterification reaction between sodium lignin sulfonate and MDI to form a polyurethane shell, which is hydrophobic and can prevent the migration of flame retardant particles from the matrix under humid conditions.

[0062] It can be concluded from Table 5 that the various properties of the rigid polyurethane foam materials of Examples 7 to 12 are better than those of Comparative Example 1. Compared with Comparative Example 1, Example 9 has a 24.2% increase in mechanical strength, a 9.8% decrease in thermal conductivity, a 58.9% decrease in total smoke production, a 26.0% decrease in total heat release, and a 15.3% increase in limiting oxygen index. The flame retardant and moisture resistance of the modified ammonium polyphosphate flame retardant is improved; and the flame retardant does not contain aldehydes, which makes the bio-based material more environmentally friendly; it has better technical effects and can be used to simultaneously improve the mechanical, thermal insulation and flame retardant properties of rigid polyurethane foam.

[0063] like Figure 1 As shown, the surface of the unmodified APP particles is smooth and presents a three-dimensional long strip shape, while the modified APP (APP@ZL) generates a network polyurethane structure and ZIF-67 on the surface.

[0064] like Figure 2 As shown in (a), the average particle size (D50) of APP is 16.2 μm. The average particle size (D50) of APP@ZL increases to 17.8 μm, indicating that new substances are generated on the surface of APP. FT-IR tests were performed on APP and APP@ZL. Figure 2 (b) 1560cm -1 and 1505cm -1 The relatively weak absorption peaks near 1610 cm-1 come from the benzene ring vibration of lignin and MDI. -1 A new absorption peak appears, corresponding to the vibration of -n-(CO)-n- in MDI, 1640 cm -1 The absorption peak comes from C=O in polyurethane, proving that APP shows the formation of polyurethane structure, 425cm -1 The absorption peak at comes from Co-N.

[0065] like Figure 3 As shown in (a) and 3(b), after constructing an organic polyurethane shell on APP, NH4 +The binding energy peak of N in -P-NH-P- disappeared, and a new binding energy peak appeared at 399.9 eV, which was attributed to the binding energy of N in the O=C-NH- group. This result shows that lignin and MDI generate polyurethane structure on the surface of APP particles. Figure 3 As shown in (c) and 3(d), the modified APP shows a new binding energy peak at 531.8 eV, which is attributed to Co 2+ The binding with -O- indicates that APP generates binding energy with ZIF-67 on the surface.

[0066] APP has two main degradation processes, starting at about 300°C. In the first stage, the mass loss is about 20%, and the main degradation products are ammonia and water, while polyphosphoric acid and polyphosphoric acid are formed; the second stage occurs at 300-620°C, and the mass loss of APP is about 65%, which is its main degradation process. Compared with APP, APP@ZL degrades faster in the first degradation stage, which is attributed to the catalytic function of ZIF-67. As the temperature continues to rise, the degradation rate of APP@ZL decreases, showing more stable thermal properties than APP, leaving about 34.3% of carbon residue at 800°C in N2 atmosphere, which is much higher than APP, indicating that APP@ZL has stronger carbonization and thermal stability.

[0067] Figure 5 It shows the degradation stages of pure RPU, comparative example 1 and example 9 foam composite materials under N2 atmosphere. The initial thermal decomposition temperature of pure RPU foam is about 265°C. The first stage of mass loss is the degradation of the polyurethane main chain to form polyols and isocyanate precursors. Isocyanate dimers form carbodiimides and produce volatile molecules, such as carbon oxides, alcohols, amines and aldehydes. The second stage is the degradation of soft segment polyols. The third stage is the formation of residual carbon. The residual carbon layer can isolate oxygen and protect the unburned substrate inside. It can be seen from the figure that the carbonization of pure RPU foam is extremely poor, only 12.0%, and the carbon layer cannot provide sufficient protection. From Figure 5 It can be seen that the addition of APP and APP@ZL improves the carbonization of RPU foam. The carbon residue of the comparative example is 24.1%, and the carbon residue of the example is 30.2%. Obviously, compared with APP, APP@ZL has a stronger catalytic carbonization ability for RPU foam composite materials. The increase in the amount of carbon residue means a decrease in combustion and smoke release.

[0068] Depend on Figure 6 It can be concluded that when used for flame retardant rigid polyurethane foam materials, the smoke suppression performance of modified ammonium polyphosphate is significantly better than that of unmodified ammonium polyphosphate. Compared with Comparative Example 1, the total smoke production of Example 9 is reduced by 58.9%.

[0069] Depend on Figure 7It can be concluded that when used for flame retardant rigid polyurethane foam materials, the heat suppression performance of modified ammonium polyphosphate is significantly better than that of unmodified ammonium polyphosphate. Compared with Comparative Example 1, the total heat release of Example 9 is reduced by 29.4%.

Claims

1. A modified ammonium polyphosphate flame retardant having the following general structural formula: in, R1 is sodium lignin sulfonate, and R2 is selected from One of the following, R3 is 2. A method for preparing the modified ammonium polyphosphate flame retardant according to claim 1, comprising the following steps: (1) Add 44.7-74.5 parts by mass of ammonium polyphosphate, 14.6-29.1 parts by mass of cobalt nitrate hexahydrate and 300-500 parts by mass of reaction solvent I into a reaction vessel, and stir for 1-3 hours at room temperature to obtain material I; (2) Add 20.5 to 82.1 parts by mass of 2-methylimidazole to material I, stir for 8 to 12 hours at room temperature, filter, dry, and sieve to obtain material II; (3) Add 48.7-72.4 parts of material II, 8-20 parts of MDI and 300-500 parts of reaction solvent II into a reaction vessel by mass, evacuate the vessel, introduce inert gas, and stir under heating conditions for 1-3 hours to obtain material III; (4) Add 1 to 5 parts of a cross-linking agent and 8 to 30 parts of sodium lignin sulfonate to material III by weight, evacuate the mixture, introduce an inert gas, and stir under heating conditions for 6 to 8 hours to obtain material IV. (5) After the reaction is completed, the product is filtered, dried, and sieved to obtain a modified ammonium polyphosphate flame retardant product.

3. The method for preparing the modified ammonium polyphosphate flame retardant according to claim 2, characterized in that: The reaction solvent I in step (1) is selected from methanol or ethanol.

4. The method for preparing the modified ammonium polyphosphate flame retardant according to claim 2, characterized in that: The drying temperature in step (2) is 60-80° C., the filtration needs to be performed three times with solvent I, and the mesh size of the sieve used during sieving is 80-100 meshes.

5. The method for preparing the modified ammonium polyphosphate flame retardant according to claim 2, characterized in that: The reaction solvent II in step (3) is selected from ethyl acetate or dichloromethane. The reaction is carried out under the protection of an inert gas and the reaction temperature is controlled at 50-70°C.

6. The method for preparing the modified ammonium polyphosphate flame retardant according to claim 2, characterized in that: The cross-linking agent in step (4) is selected from propylene glycol or pentaerythritol. The reaction is carried out under the protection of an inert gas and the reaction temperature is controlled at 60-80°C.

7. The method for preparing the modified ammonium polyphosphate flame retardant according to claim 2, characterized in that: In the filtering step (5), the reaction solvent II is filtered three times, the drying temperature is 50-70° C., and the mesh size of the sieve used during sieving is 80-100 meshes.

8. Use of the modified ammonium polyphosphate flame retardant according to claim 1 in rigid polyurethane foam materials.

Citation Information

Cited By

  • Bifunctional ammonium polyphosphate flame retardant, preparation method thereof and flame-retardant thermoplastic polyurethane composite material

    CN121991411A

  • Core-shell flame-retardant composite material, preparation method therefor and use thereof

    WO2026199760A1